Leukocyte ?7 integrin targeted by Krüppel-like factors - Alles, Melanie; Turchinovich, Gleb; Zhang, Pumin; Schuh, Wolfgang; Agenes, Fabien; Kirberg, Joerg (Journal of Immunology, 2014)
Constitutive expression of Krüppel-like factor 3 (KLF3, BKLF) increases marginal zone (MZ) B cell numbers, a phenotype shared with mice lacking KLF2. Ablation of KLF3, known to interact with serum response factor (SRF), or SRF itself, results in fewer MZ B cells. It is unknown how these functional equivalences result. In this study, it is shown that KLF3 acts as transcriptional repressor for the leukocyte-specific integrin ?7 (Itgb7, Ly69) by binding to the ?7 promoter, as revealed by chromatin immunoprecipitation. KLF2 overexpression antagonizes this repression and also binds the ?7 promoter, indicating that these factors may compete for target sequence(s). Whereas ?7 is identified as direct KLF target, its repression by KLF3 is not connected to the MZ B cell increase because ?7-deficient mice have a normal complement of these and the KLF3-driven increase still occurs when ?7 is deleted. Despite this, KLF3 overexpression abolishes lymphocyte homing to Peyer's patches, much like ?7 deficiency does. Furthermore, KLF3 expression alone overcomes the MZ B cell deficiency when SRF is absent. SRF is also dispensable for the KLF3-mediated repression of ?7. Thus, despite the shared phenotype of KLF3 and SRF-deficient mice, cooperation of these factors appears neither relevant for the formation of MZ B cells nor for the regulation of ?7. Finally, a potent negative regulatory feedback loop limiting KLF3 expression is shown in this study, mediated by KLF3 directly repressing its own gene promoter. In summary, KLFs use regulatory circuits to steer lymphocyte maturation and homing and directly control leukocyte integrin expression.
EVALuna2:13624